2015
DOI: 10.1080/02681102.2015.1052359
|View full text |Cite
|
Sign up to set email alerts
|

Are Street Vendors Really Innovative Toward Self-service Technology?

Abstract: Street vending has acquired great importance in present times. This study attempts to link consumer innovativeness (CI) to street vending -an ancient occupation now emerging as a new market form using technology and innovation. The study investigates the behavior of street vendors (a group hypothesized to enjoy more innovativeness than those with similar socioeconomic backgrounds) regarding adoption of self-service technologies (SSTs) in the retail banking industry. In addition to primary research instruments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
10
0
2
Order By: Relevance
“…A recent study (Kaushik & Rahman, ) about the use of ATMs, Internet banking, and self‐service kiosks among the street vendors in New Delhi showed poor usage, except for ATMs. Another study (Masiero, ) also reinforced the limited use of digital tools like mobile banking tools by the informal enterprises in Bangalore while attempting to integrate into a cashless society.…”
Section: Use Of Icts and Impact On Informal Enterprises In Indiamentioning
confidence: 99%
“…A recent study (Kaushik & Rahman, ) about the use of ATMs, Internet banking, and self‐service kiosks among the street vendors in New Delhi showed poor usage, except for ATMs. Another study (Masiero, ) also reinforced the limited use of digital tools like mobile banking tools by the informal enterprises in Bangalore while attempting to integrate into a cashless society.…”
Section: Use Of Icts and Impact On Informal Enterprises In Indiamentioning
confidence: 99%
“…Usually, mutual interactions foster interpersonal relationships between customers and service employees (Kaushik & Rahman, 2015c), but this interaction and interpersonal relationships are absent during SST usage. However, this interaction is quite necessary for understanding the technicalities of service delivery through SSTs (Seth et al, 2005).…”
Section: Need For Interaction and Perceived Performance Risk As Predimentioning
confidence: 99%
“…Dabholkar [43] mentioned the importance of human interaction for a customer in a service encounter; the study indicated that an SST fails to satisfy a customer's desire to interact with the service staff, which negatively affects its expected quality. Interaction promotes the interpersonal relationship between customers and the service staff [44]. However, the use of SST does not facilitate an interpersonal relationship and interaction, which is very essential for understanding the technology of service delivery through SST [17].…”
Section: Need For Interactionmentioning
confidence: 99%